Մատաղ սերնդի հայրենասիրական դաստիարակության հարցերը Սերո Խանզադյանի ստեղծագործություններում - Մելինե Գիլավյան (ՀՀ ԳԱԱ հրատ.)
В настоящей статье рассматриваются рассказы видного армянского писателя, написанные для детей или вошедшие в круг их чтения, а также повести “Шесть ночей”, “Мертвые вспоминают”, “Аракс мутнеет”. Gilavyan in this article reviews some of the short stories of renowned writer Sero Khanzadyan and in particular the novellas, "Six nights", "The Dead Remember" and "Araks is Blurry" as well.
Keywords: Theory and practice of education; Primary Education; Language and Literature